Indoor air quality and climate change impacts on air-conditioning and mechanical ventilation (ACMV) systems in commercial buildings in the tropics / Syafawati Hasbi - Syafawati, Hasbi (2013)
Climate change will imply new condition for building industry and sufficient information on the possible implications will be crucial in years to come to mitigate the potential impacts. Numerous studies have been conducted to assess building’s energy consumption in the future; however, some of the studies do not take into account climatic variability and occupant’s reaction towards the temperature shift. For the indoor air quality study, case studies were done at the green building which employed the radiant slab cooling and commercial non-green building with conventional cooling system. The field measurement was carried out at the Energy Commission building in Putrajaya, Malaysian Green Technology Corporation building in Bangi and Construction Research Institute of Malaysia in Cheras. Standard procedure given by the ASHRAE (American Society of Heating, Refrigeration and Air-Conditioning Engineers) was employed during the field work measurement. For objective measurement, parameters such as the room temperature, relative humidity, air velocity and the concentration of indoor pollutants were collected. The results were then compared to the MS1525:2007 and ASHRAE Standard-55 and 62 2010. The results showed that the indoor air quality in the building were within the acceptable standard recommended by the Malaysian Standard (MS 1525:2007) and ASHRAE Standard 55 and 62-2010 except for the relative humidity in the non-green building and air velocity for the green buildings Case study also has been systematically done for the climate change impacts on the air conditioning system at the Construction Research Institute of Malaysia building taken into consideration the temperature, humidity and cooling load of the building. The TRNSYS simulation results showed that the total maximum cooling load required in the years of 2000, 2020, 2050 and 2080 are 297000 kJ/hr, 305000 kJ/hr, 321000 kJ/hr and 332000 kJ/hr. The results were then compared with the year 2000 as the reference year. It is observed that the maximum cooling load needed in the year of 2020, 2050 and 2080 increase by 2.96%, 8.08% and 11.7% respectively. As the design cooling load is 211011 kJ/hr, the system is predicted to be unable to provide sufficient cooling load to the office space in the future as the maximum cooling load needed in the year 2080 is 332000 kJ/h. The air distribution study was also conducted at the same building. The air flow and velocity were measured at selected locations in the office building and compared with the Computational Fluid Dynamics (CFD) simulation. Both results showed that the indoor air flows are mixture of low R and fully turbulent flows. The incapability of the existing system to meet the cooling load requirement will lead to overheating in the office space and affects occupant health and performance. Regular maintenance and retrofitting are required in order to ensure that the system is able to provide sufficient cooling for the space. This study is undertaken to initiate the environmental awareness among the building designer with the issue that is often ignored.